Higher ruminal pH increases in vitro digestion of diets containing dried distillers grains with solubles - S. Uwituze; J.M. Heidenreich; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2009)
Advantages of steam flaking grain are less with respect to growth performance and diet digestion when a portion of distillers grains is substituted for grain. Ruminal pH typically is lower in cattle fed flaked-grain diets than in cattle fed rolled-grain diets. Ruminal pH for cattle fed finishing diets based on steam-flaked corn is observed below pH 6.0. Previous research observed a 5% decrease in digestion of organic matter when 13% distillers grains (dry-matter basis) was added to steam-flaked corn finishing diets. A decline in ruminal pH below 6.2 reduces activity of ruminal fiber-digesting organisms. Furthermore, ruminal protein digestion declines with pH below 5.5. It is plausible that low ruminal pH may restrict digestion of distillers grains in flaked-grain diets. The objective of this study was to examine effects of pH on in vitro fermentative activity of ruminal contents from cattle adapted to a finishing diet containing 25% dried distillers grains (dry-matter basis).
Keywords: Cattlemen' s Day; 2009; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1010; Kansas Agricultural Experiment Station contribution; no. 09-168-S; Beef; Cattle; Ruminal pH; Distillers grains